Penggunaan Alat Peraga untuk Menigkatkan Literasi Sains Siswa pada Materi Bagian-Bagian Tumbuhan dalam Pembelajaran IPAS Kelas IV - Sofa Sofiana; Ade Maftuh; Rizki Hadiwijaya Zulkarnaen (Lembaga Bale Literasi, 2026)
Science is a branch of science that is factual, either in the form of facts or events that are interconnected by cause and effect. Science was initially obtained through experiments (inductive) but over time, it was also developed with theory (deductive). Science in schools aims to ensure that students understand the processes and products of science, have a scientific attitude, and are able to become ethical citizens who are sensitive to environmental issues. The word